INTEGRATION OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN PUBLIC ENGINEERING AND ARCHITECTURE ACTIVITIES: A CASE STUDY AT THE FEDERAL INSTITUTE OF SANTA CATARINA (REMUNOM, 2025)
This article aims to analyze and evaluate the technological tools available and used in the development of engineering and architecture activities within the Project and Construction Supervision Coordinations of the Instituto Federal Catarinense (IFC), as well as their interaction with generative artificial intelligence. The theoretical framework encompasses key concepts, benefits, advantages, and limitations related to the use of such technologies, examining their implications for institutional performance. The study presents an integrated analysis of the systems and software applied to the IFC’s technical activities, focusing on four fundamental dimensions: professional training, licensing model, advantages and disadvantages of use, and intellectual property of the projects developed. The methodology combines bibliographic research and field studies, including interviews and questionnaires applied to professionals from the analyzed departments. The results highlight the need for each coordination to maintain a specific set of technological systems, coupled with AI and continuous training programs, to ensure technical updating and operational efficiency. It was also verified that the use of specialized software for project design and construction supervision contributes to legal security, financial sustainability, and the standardization of institutional practices. Theoretical and practical implications provide relevant insights for improving technological management in public institutions. The originality of this research lies in the comparative analysis between on-site and remote activities, emphasizing the importance of technological tools and artificial intelligence as structural elements for the modernization of public administration in engineering and architecture.